Overview of eating disorders based on the Eating Attitudes Test (EAT-26) questionnaire (Research, Society and Development, 2024)
Introduction: Eating Disorder (ED) has proven to be a persistent problem both in the country and globally. This psychiatric condition is characterized by persistent and abnormal patterns of eating or eating behavior. Thus, ED leads to inadequate consumption and/or malabsorption of nutrients, significantly affecting the individual's mental, physical, nutritional, and social health. Objective: To analyze the use of the EAT-26 questionnaire in the research of eating disorders. Methodology: The research was carried out in July 2024, 26 articles were found in the databases, 11 of which were selected. Result: From the results found, it was possible to observe that the incidence of ED is higher in young females. In addition, studies have shown a higher prevalence among students in the health area, and most of these studies were carried out in the Middle East. Conclusion: The use of the EAT-26 questionnaire has proven effective in identifying eating disorders. Thus, it can be concluded that eating disorders are an important issue. Adopting interventions that address the root cause of the problem is crucial, taking into account factors such as gender, body mass index (BMI) and the high-stress academic environment.